Microlepidoptera of Hong Kong: Oecophoridae II: description of three new species of the genus Variacma Wang - Wang, Shu-Xia; Yuan, Gai-Xia; Kendrick, Roger C. (Zootaxa, 2011)
Three new species of the genus Variacma Wang are described from Hong Kong, China: V. hongkongensis sp. nov., V. bifariafera sp. nov. and V. tomentosa sp. nov. The female is recorded for the first time for the genus and the generic characters are redescribed. Images of adults and genitalia are provided, along with a key to all the known species based on the male genitalia.